Peningkatan Pengetahuan Ibu Tentang Kebersihan Gigi dan Mulut Anak TK Melalui Penyuluhan - Ratih Larasati (Health Community Engagement, 2022)
The health of the child's teeth and mouth is a factor that must be considered as early as possible because it can affect the growth of teeth at a later age. The proportion of daily brushing behavior in the ≥ 3-year-old population in East Java is very high, but proper brushing behavior in the population of ≥ 3 years is still very lacking. The results of previous studies prove that the percentage of the mother's actions in the maintenance of the health of the teeth and mouth of the child is good, but the health status of the child's teeth and mouth is bad. The problem that exists in kindergarten children in Kemayoran village of Krembangan Subdistrict is the low health status of the child's teeth and mouth, so it is considered necessary for the mother of the kindergarten child to be given counseling about the maintenance of dental and oral hygiene of the child. The purpose of community service is to increase the mother's knowledge of kindergarten children about the maintenance of dental and oral hygiene of children. The methods used extension, demonstration, and simulation of brushing teeth. There is an increase in maternal knowledge about the maintenance of dental and oral hygiene of children, but there are still many mothers who do not know the correct standing position when brushing children's teeth and the benefits of checking teeth regularly. This activity proves that counseling can increase the knowledge of mothers and kindergarten teachers.